Adaptive Fault-Tolerant Tracking Control for Linear and Lipschitz Nonlinear Multi-Agent Systems - Zuo, Zhiqiang; Zhang, Jun; Wang, Yijing (IEEE transactions on industrial electronics (1982), 2015)
This paper considers the problem of fault-tolerant tracking control for linear and Lipschitz nonlinear multi-agent systems subject to actuator faults and the leader's bounded unknown input. The communication topology is the undirected subgraph with directed connections between the leader and the followers. Based on the relative states of neighbors and a general actuator fault model, an adaptive fault-tolerant control protocol is proposed to compensate for the failure effects on consensus tracking where the feedback matrices update the parameters by the online estimation of actuator faults. The criteria of reaching consensus tracking despite the actuator faults for both linear and Lipschitz nonlinear agents are derived, respectively. Finally, two examples are included to illustrate the theoretical results.